λ–Algebra with Some of Their Properties - Ebrahim, Hassan Hussien; Ali, Rusul Abd Al_salam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The objective of this paper is, firstly, we study a new concept noted by algebra and discuss the properties of this concept. Secondly, we introduce a new concept related to the algebra such as smallest algebra. Thirdly, we introduce the notion of the restriction of algebra on a nonempty subset  of and investigate some of its basic properties. Furthermore, we present the relationships between field, monotone class, field and algebra. Finally, we introduce the concept of measure relative to the algebra and prove that every measure relative to the   is complete.